2015
DOI: 10.1371/journal.pgen.1005346
|View full text |Cite
|
Sign up to set email alerts
|

TopBP1 Governs Hematopoietic Stem/Progenitor Cells Survival in Zebrafish Definitive Hematopoiesis

Abstract: In vertebrate definitive hematopoiesis, nascent hematopoietic stem/progenitor cells (HSPCs) migrate to and reside in proliferative hematopoietic microenvironment for transitory expansion. In this process, well-established DNA damage response pathways are vital to resolve the replication stress, which is deleterious for genome stability and cell survival. However, the detailed mechanism on the response and repair of the replication stress-induced DNA damage during hematopoietic progenitor expansion remains elus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 86 publications
1
23
0
Order By: Relevance
“…The constitutive activation of P53 is harmful for the stemness of HSPCs (Liu et al, 2010;Wang et al, 2011), whereas HSPCs in the p53 mutant are relatively normal (Lotem and Sachs, 1993). Here, we found that the transcript of p53 was specifically increased in the CHT region of rpc9 mutants, mediating HSPC impairments, which is similar to two works reporting that HSPC defects in zebrafish embryos deficient in TopBP1 (topoisomerase II β binding protein 1, involved in DNA replication and DNA damage) or the ribosome protein Rpl11 could be rescued by knockdown of p53 (Danilova et al, 2011;Gao et al, 2015). Although apoptosis signals in the CHT region were decreased upon p53 deficiency, the proliferation signals between rpc9 −/− embryos with or without intact p53 signaling showed no significant difference, suggesting that increased apoptosis but not decreased proliferation was responsible for HSPC impairment in rpc9 mutants.…”
Section: Discussionsupporting
confidence: 89%
“…The constitutive activation of P53 is harmful for the stemness of HSPCs (Liu et al, 2010;Wang et al, 2011), whereas HSPCs in the p53 mutant are relatively normal (Lotem and Sachs, 1993). Here, we found that the transcript of p53 was specifically increased in the CHT region of rpc9 mutants, mediating HSPC impairments, which is similar to two works reporting that HSPC defects in zebrafish embryos deficient in TopBP1 (topoisomerase II β binding protein 1, involved in DNA replication and DNA damage) or the ribosome protein Rpl11 could be rescued by knockdown of p53 (Danilova et al, 2011;Gao et al, 2015). Although apoptosis signals in the CHT region were decreased upon p53 deficiency, the proliferation signals between rpc9 −/− embryos with or without intact p53 signaling showed no significant difference, suggesting that increased apoptosis but not decreased proliferation was responsible for HSPC impairment in rpc9 mutants.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that the reduced signal for HSCs or hematopoietic stem progenitor cells (HSPCs) could be caused by apoptosis (28). TUNEL assays displayed a significantly increased number of apoptotic EGFP-positive HSPCs in the caudal hematopoietic tissue region of adtrp1 morphants compared with that of Std-MO morphants at 3 dpf ( Fig.…”
Section: Adtrp1 Is Involved In Definitive Hematopoiesismentioning
confidence: 84%
“…25 Immunofluorescence double staining was performed as described previously, 52 with chicken anti-GFP (1:400; Life Technologies) and rabbit anti-phospho-histone 3 (pH3) antibodies (1:250; Abcam). AlexaFluor 488-conjugated anti-chicken secondary antibody (1:1000; Life Technologies) and AlexaFluor 594-conjugated anti-rabbit secondary antibody (1:1000; Life Technologies) were used to reveal primary antibodies.…”
Section: Confocal Microscopy and Immunofluorescence Stainingmentioning
confidence: 99%
“…We took noninjected and hl-ztfec-injected cmyb:GFP embryos and stained for both GFP and phospho-Histone 3 (pH3) to quantify proliferating HSCs, as previously described 52 ( Figure 2H-O). At 3 dpf, hl-ztfec mRNA injection significantly increased the number of proliferating HSCs (cmyb:GFP 1 /pH3 1 ) within the CHT, but only led to a small and nonsignificant increase at 4 dpf ( Figure 3H, L-O), which was confirmed using cd41:eGFP transgenic embryos and counting the number of proliferating HSCs (cd41:…”
Section: Tfec-p2 Specifically Marks the Endothelial Niche In The Chtmentioning
confidence: 99%